Persistent deficits in hippocampal synaptic plasticity accompany losses of hippocampus-dependent memory in a rodent model of psychosis - Wiescholleck, Valentina; Manahan-Vaughan, Denise (Frontiers in Integrative Neuroscience, 2013)
Irreversible N-methyl-D-aspartate receptor (NMDAR) antagonism is known to provoke symptoms of psychosis and schizophrenia in healthy humans. NMDAR hypofunction is believed to play a central role in the pathophysiology of both disorders and in an animal model of psychosis, that is based on irreversible antagonism of NMDARs, pronounced deficits in hippocampal synaptic plasticity have been reported shortly after antagonist treatment. Here, we examined the long-term consequences for long-term potentiation (LTP) of a single acute treatment with an irreversible antagonist and investigated whether deficits are associated with memory impairments. The ability to express long-term potentiation (LTP) at the perforant pathway – dentate gyrus synapse, as well as object recognition memory was assessed 1, 2, 3 and 4 weeks after a single -treatment of the antagonist, MK801. Here, LTP in freely behaving rats was significantly impaired at all time-points compared to control LTP before treatment. Object recognition memory was also significantly poorer in MK801-treated compared to vehicle-treated animals for several weeks after treatment. Histological analysis revealed no changes in brain tissue. Taken together, these data support that acute treatment with an irreversible NMDAR antagonist persistently impairs hippocampal functioning on behavioral, as well as synaptic levels. The long-term deficits in synaptic plasticity may underlie the cognitive impairments that are associated with schizophrenia-spectrum disorders.